2011
DOI: 10.1007/s11661-011-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitride Formation and Excess Nitrogen Uptake After Nitriding Ferritic Fe-Ti-Cr Alloys

Abstract: The microstructure of the nitrided zone of Fe-Ti-Cr alloys, containing a total of 0.30 at. pct (Ti + Cr) alloying elements, with varying Ti/Cr atomic ratio (0.45, 0.87, and 1.90), was investigated by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The stable TiN and CrN nitrides did not precipitate after nitriding. Instead, ultrafine, metastable, mixed Ti 1-x Cr x N nitride precipitates developed in the nitrided zone: The precipitates were of platelet morphology (length £30 nm and thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It is rather difficult to unambiguously determine the crystal structures of alloy nitrides because the diffraction patterns (upper right corner insets) are not clear. According to the previous reports on the nitriding of Fe-Al-Cr [17] and Fe-Cr-Ti alloys, [20] these precipitates should have B1 structure and a Backer-Nutting orientation relationship with the a matrix. Small spots that cannot be indexed to either a or B1 precipitates may correspond to an oxide layer on the thin film.…”
Section: B Microstructure Characterizationmentioning
confidence: 90%
See 2 more Smart Citations
“…It is rather difficult to unambiguously determine the crystal structures of alloy nitrides because the diffraction patterns (upper right corner insets) are not clear. According to the previous reports on the nitriding of Fe-Al-Cr [17] and Fe-Cr-Ti alloys, [20] these precipitates should have B1 structure and a Backer-Nutting orientation relationship with the a matrix. Small spots that cannot be indexed to either a or B1 precipitates may correspond to an oxide layer on the thin film.…”
Section: B Microstructure Characterizationmentioning
confidence: 90%
“…[17][18][19] They also found that (Cr, Ti) mixed nitrides are formed in the nitriding of Fe-Cr-Ti alloys. [20] Both V and Ti atoms have a strong affinity with N atoms. Therefore, the similar nitriding behavior between the Fe-Cr-V and Fe-Cr-Ti alloys can be understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitriding time required to fully precipitate both Cr and Mo as NaCl-type ternary nitride in the ternary Fe-1Cr-1Mo alloy is much shorter than for the precipitation of Mo as NaCl-type binary nitride in the binary Fe-1Mo alloy [7]. nitrides based on kinetic constraints, was given previously for the mixed nitrides formed in nitrided ternary Fe-Cr-Ti [70] and Fe-Cr-Al [44], [71], [72] alloys. Indeed, the mixed, cubic NaCl-type (Cr,Ti)N and (Cr,Al)N nitrides, as holds for the mixed (Cr,Mo)N x nitride of the present study as well, were found to be metastable in these systems: decomposition into the separate binary nitrides can take place at elevated temperature [72]- [74].…”
Section: Formation Of Ternary (Cr ½ Mo ½ )N ¾ Plateletsmentioning
confidence: 92%
“…Recent studies on ternary Fe-Cr-Al [63] and Fe-Cr-Ti [64] alloys showed that in the ternary alloys also cubic NaCl-type, ''mixed'' ternary CrxAl 1-X N, and Cr x Ti 1-X N nitride platelets develop along {100} lattice planes of the ferrite matrix and in accordance with a Baker-Nutting orientation relationship. Similar research performed by Kang et al [65] in quaternary Fe-based alloys also allowed to identify ''mixed'' nature of a quaternary (Cr X ,V Y , Mo 1-X-Y )N nitride…”
Section: Discontinuous Precipitation and Discontinuous Coarsening In mentioning
confidence: 96%